2011
DOI: 10.1002/aenm.201000074
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of the Amorphous Silicon Microstructure on the Grain Size of Solid Phase Crystallized Polycrystalline Silicon

Abstract: In this paper the effect of the microstructure of remote plasma‐deposited amorphous silicon films on the grain size development in polycrystalline silicon upon solid‐phase crystallization is reported. The hydrogenated amorphous silicon films are deposited at different microstructure parameter values R* (which represents the distribution of SiHx bonds in amorphous silicon), at constant hydrogen content. Amorphous silicon films undergo a phase transformation during solid‐phase crystallization and the process res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…10 Within the field of thin film silicon-based solar cells, poly-crystalline silicon (poly-Si) receives attention because it couples the potential for high conversion efficiency and lower production costs. One of the approaches toward poly-Si is plasma deposition of amorphous silicon followed by solidphase crystallization (SPC), 11,12 which has delivered efficiencies up to 10%; 13,14 for example, CSG Solar 15 has achieved an efficiency of 10.4% by developing a 2.5 lm-thick poly-Si on glass, which was also confirmed by studies reported by Green et al 15 In this case, the TCO can be applied as front contact and aluminum-doped zinc oxide (ZnO:Al) is often referred to as a valid alternative to, e.g., indium tin oxide. The ZnO is considered appealing due to the relatively low cost, high abundance, non-toxicity, 16,17 resistance to H 2 etching, 18,19 and, under specific conditions, surface texturing for light management/trapping.…”
mentioning
confidence: 99%
“…10 Within the field of thin film silicon-based solar cells, poly-crystalline silicon (poly-Si) receives attention because it couples the potential for high conversion efficiency and lower production costs. One of the approaches toward poly-Si is plasma deposition of amorphous silicon followed by solidphase crystallization (SPC), 11,12 which has delivered efficiencies up to 10%; 13,14 for example, CSG Solar 15 has achieved an efficiency of 10.4% by developing a 2.5 lm-thick poly-Si on glass, which was also confirmed by studies reported by Green et al 15 In this case, the TCO can be applied as front contact and aluminum-doped zinc oxide (ZnO:Al) is often referred to as a valid alternative to, e.g., indium tin oxide. The ZnO is considered appealing due to the relatively low cost, high abundance, non-toxicity, 16,17 resistance to H 2 etching, 18,19 and, under specific conditions, surface texturing for light management/trapping.…”
mentioning
confidence: 99%
“…Recently, we also specifically addressed the relationship between R* and the grain size development in poly-Si obtained upon SPC of a-Si:H films deposited in a remote plasma configuration, i.e., the expanding thermal plasma (ETP). 22 The grain size in poly-Si was found to increase (from 0.4 lm to 1.5 lm) with increasing R* (from 0.1 to 0.45). 22 Furthermore, when referring to the crystallization kinetics studies, Mahan et al…”
mentioning
confidence: 86%
“…22 The grain size in poly-Si was found to increase (from 0.4 lm to 1.5 lm) with increasing R* (from 0.1 to 0.45). 22 Furthermore, when referring to the crystallization kinetics studies, Mahan et al…”
mentioning
confidence: 86%
“…22 The grain size in poly-Si was found to increase from 0.4 lm to 1.5 lm, with an increase in R* from 0.1 to 0.45. 15 Therefore, these preliminary considerations suggest that a high growth rate and a high R* would represent the ideal combination for the development of poly-Si films is reported.…”
Section: Introductionmentioning
confidence: 94%
“…The ETP-CVD setup is described in detail elsewhere. 16 The pressure was varied in the range of 0.15-1 mbar and the substrate temperature (T sub ) was set to 450 C. The choice of this substrate temperature setting in comparison with the studies previously carried out at 200 C, 15 is based on the-often reported in literature 17 -compromise between high growth rate and porosity in the deposited layer. In the specific case of a-Si:H, films deposited at low substrate temperature and at high growth rate are prone to oxidation, which hampers the crystallization process.…”
Section: Introductionmentioning
confidence: 99%